Comparison of Vocational Students’ Conceptual Understanding in Acid-Base Titration Using Virtual Lab-Based Learning and Lab-Based Learning with Chemical and Natural Indicators - Hartinah Pratiwi; Alvin Annayya Habibah; Kurnia Larasati; Anugrah Ricky Wijaya (Department of Chemistry, Universitas Negeri Malang, 2025)
This study compared the effectiveness of Virtual Lab-Based Learning (VLL) and Lab-Based Learning (LBL) in improving students’ conceptual understanding of acid-base using chemical and natural indicators. A quantitative quasi-experimental design with a pretest-posttest control group was implemented involving 30 vocational high school students from the Industrial Chemistry program at SMK PGRI 3 Malang, divided equally into two groups. The LBL group conducted hands-on laboratory experiments, while the VLL group utilized the ChemCollective virtual simulation platform. Both groups studied the same topic with equal instruction time and guidance from the same teacher. The results indicated that both learning models significantly improved students’ conceptual understanding of acid-base titration, with the LBL group achieving a higher post-test increase (74.06%) than the VLL group (62.26%). This suggests that direct laboratory practice fosters greater procedural accuracy, conceptual comprehension, and cognitive engagement. However, VLL remains a useful alternative for schools with limited laboratory access, providing an interactive means for students to visualize titration steps, color changes, and pH variations. The incorporation of natural pigments from red cabbage and hibiscus further enhanced student interest and contextual learning outcomes. Despite these promising results, the limited sample size constrains the generalization of findings, and future studies with larger, more diverse samples are recommended to validate the consistency of these results across broader educational contexts.